2010
DOI: 10.17660/actahortic.2010.868.8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Method and Level of Nitrogen Fertilizer Application on Soil Ph, Electrical Conductivity, and Availability of Ammonium and Nitrate in Blueberry

Abstract: Blueberries (Vaccinium spp.) require low soil pH and prefer N primarily as NH 4 + for optimum production. Nitrogen fertilizer methods and rates were evaluated in a new field of 'Bluecrop' blueberry (Vaccinium corymbosum L.) to determine their effects on soil pH and availability of NH 4 + and NO 3 -in soil solution. Treatments included four application methods (split fertigation, continuous fertigation, and two non-fertigated controls) and four rates of N application (0, 50, 100, and 150 kg·ha -1 N). Fertigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 0 publications
2
19
0
Order By: Relevance
“…Bryla and Machado (2011) found that while fertigation was less efficient than broadcast fertilizer at promoting growth at low N rates, it resulted in more growth when high rates of N were applied. Again, the reason was attributed to an increase in soil EC and subsequent salinity when using a high rate of granular ammonium sulphate, which was not evident when plants were fertigated with liquid urea (Bryla et al 2010).…”
Section: Fig 5 (Continued)mentioning
confidence: 99%
“…Bryla and Machado (2011) found that while fertigation was less efficient than broadcast fertilizer at promoting growth at low N rates, it resulted in more growth when high rates of N were applied. Again, the reason was attributed to an increase in soil EC and subsequent salinity when using a high rate of granular ammonium sulphate, which was not evident when plants were fertigated with liquid urea (Bryla et al 2010).…”
Section: Fig 5 (Continued)mentioning
confidence: 99%
“…It is well known that blueberries develop well in acidic soils with a pH of 4.5 to 5.5 and with low levels of fertility (Korcak, 1988;Mainland, 2012;Retamales and Hancock, 2012). Some authors recommend nutrient solutions with low electrical conductivity (EC) between 0.45 and 1.5 dS · m -1 (Ameri et al, 2012;Bryla et al, 2010;Ingestad, 1973;Machado et al, 2014). However, the optimal EC of the nutrient solution for the cultivation of blueberries in soilless culture has not yet been determined (Voogt et al, 2014).…”
mentioning
confidence: 99%
“…, (Hagin and Lowengart, 1996;Li et al, 2003;Hartz et al, 2005). (Finn and Warmund, 1996;Vargas and Bryla, 2015), (Bryla and Machado, 2011), (Glonek and Komosa, 2004), (Ehret et al ., 2014), (Bryla et al ., 2008) .…”
mentioning
confidence: 99%